Characteristics of older patients in the largest French psychiatric emergency centre - Pham-Scottez, Alexandra; Gallarda, Thierry; Calvez, Mathilde; Silva, Jérôme; Barruel, David; Masson, Valérie Dauriac-Le; Lahaye, Justine; Perquier, Florence; Sarazin, Marie; Gourevitch, Raphaël (Frontiers in Psychiatry, 2023)
Despite an increasing number of adults older than 60 years with psychiatric disorders, there are few studies on older patients in psychiatric emergencies and no European data. We aimed to describe the population of patients aged 60 years and older who presented to the main French psychiatric emergency centre and identify predictors of psychiatric hospitalisation. This monocentric study included 300 consecutive patients aged 60 years and older. Patients presenting because of psychiatric emergencies were frequently female and lived autonomously. More than 40% had a history of at least one psychiatric hospitalisation and 44% had consulted a psychiatrist in the previous six months. The most common reasons for consultation were depression, anxiety, sleep disorders and suicidal thoughts. Psychiatric disorders were mainly mood disorders; neurotic, stress-related and somatoform disorders; and schizophrenic, schizotypal and delusional disorders. Only 10% had a diagnosis of organic mental disorders. Overall, 39% of the patients were admitted to the psychiatric hospital. Factors predicting hospitalisation were a history of psychiatric hospitalisation, suicidal thoughts and a diagnosis of a mood disorder or schizophrenia/schizotypal/delusional disorder. In conclusion, among people aged 60 years and older who consulted for psychiatric emergencies, 39% had to be hospitalised in psychiatry and only psychiatric factors influenced the decision to hospitalise. Our study highlights the need for further studies of older people in psychiatric emergencies in Europe, to anticipate the needs of this specific population and adapt multidisciplinary mental health care.